Measuring Customer Loyalty Through Service Quality and Customer Satisfaction at Wirun Pharmacy in Purworejo Regency - Safina Yuliani; Hesti Respatiningsih; Dewi Shanti Nugrahani (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the extent to which service quality and customer satisfaction influence consumer loyalty at Wirun Pharmacy, Purworejo Regency. The research adopts a quantitative explanatory approach, employing multiple linear regression, t-test, F-test, and coefficient of determination analysis as its analytical techniques. The sample of 104 respondents was determined using the Lemeshow formula to ensure representativeness. The findings of the study demonstrate that both service quality and customer satisfaction exert a positive and significant influence on customer loyalty. Among these two factors, customer satisfaction emerges as the most dominant variable shaping loyalty, highlighting its central role in determining whether consumers remain committed to continuing their transactions with the pharmacy. These results suggest that ensuring customer satisfaction is not only an outcome but also a strategic tool to foster long-term loyalty. Furthermore, the research underscores the necessity for pharmacy service providers to maintain high standards of service quality, while simultaneously focusing on customer-oriented strategies that prioritize satisfaction. Continuous improvement in aspects such as responsiveness, reliability, assurance, and empathy becomes essential to enhance consumer experiences. Practical implications of the findings provide valuable insights for pharmacy managers in designing service innovations, implementing customer-centered policies, and strengthening retention strategies in a competitive healthcare service environment. Overall, this study contributes to the understanding of how service-related factors interact to create sustainable consumer loyalty, offering guidance for both academic research and managerial practices in the field of pharmacy services. The study also highlights the relevance of customer relationship management, innovation, and effective communication as critical elements to sustain competitive advantage in the dynamic pharmaceutical industry.